Pengaruh Stratifikasi Sosial Terhadap Akses Pendidikan Dasar di Wilayah Perkotaan dan Pedesaan - Hanifah Fitriyani; Siti Umayyah; Nanda Fairuz Fatin; Arum Fatayan (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Education plays a crucial role in determining an individual's social position in society and serves as a means to promote social mobility. However, the reality in Indonesia reveals a significant disparity in access to education between urban and rural areas due to social stratification. This study aims to examine how social stratification affects access to basic education, particularly in the context of geographical and socioeconomic differences. Using a descriptive qualitative approach through literature review, this article analyzes relevant literature on educational inequality, its impact on school-aged children, and potential strategies to address the issue. The findings indicate that children in rural areas face various challenges, including limited educational facilities, a shortage of qualified teachers, and difficult geographical conditions. Meanwhile, in urban areas, although facilities are more complete, economic factors remain a major barrier for underprivileged groups. This inequality leads to low school participation, poor literacy, and decreased learning motivation among students. Therefore, comprehensive strategies such as equitable zoning policies, scholarships, development of educational infrastructure, and cross-sector collaboration are needed to ensure equal and inclusive access to education for all members of society.